Esterification of Palm Fatty Acid Distillate using Sulfonated Alumina - Nazratul Zaheera, Abdul Kapor; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim (Panoply Consultancy, 2017)
With increasing environmental concern around the world, alternative energy became more and more important. Biodiesel is one of favorable alternative fuel which has been implemented widely by blended to fossil diesel. Palm fatty acid distillate, by-product from palm oil refinery is one of sources utilized to produce biodiesel. As the palm fatty acid distillate has high free fatty acid content, the catalyst used should be acidic in nature. Sulfonated alumina catalyst, having pH between 1.8 and 3.0, prepared by wet impregnation method using sulfuric acid, is used to aid the esterification process. Variation of reaction time, methanol to PFAD molar ratio and catalyst amount were implemented to get the highest possible conversion of >80%.